Actinorhizal Signaling Molecules: Frankia Root Hair Deforming Factor Shares Properties With NIN Inducing Factor - Cissoko, Maimouna; Hocher, Valérie; Gherbi, Hassen; Gully, Djamel; Carré-Mlouka, Alyssa; Sane, Seyni; Pignoly, Sarah; Champion, Antony; Ngom, Mariama; Pujic, Petar; Fournier, Pascale; Gtari, Maher; et al. (Frontiers in Plant Science, 2018)
Actinorhizal plants are able to establish a symbiotic relationship with Frankia bacteria leading to the formation of root nodules. The symbiotic interaction starts with the exchange of symbiotic signals in the soil between the plant and the bacteria. This molecular dialogue involves signaling molecules that are responsible for the specific recognition of the plant host and its endosymbiont. Here we studied two factors potentially involved in signaling between Frankia casuarinae and its actinorhizal host Casuarina glauca: (1) the Root Hair Deforming Factor (CgRHDF) detected using a test based on the characteristic deformation of C. glauca root hairs inoculated with F. casuarinae and (2) a NIN activating factor (CgNINA) which is able to activate the expression of CgNIN, a symbiotic gene expressed during preinfection stages of root hair development. We showed that CgRHDF and CgNINA corresponded to small thermoresistant molecules. Both factors were also hydrophilic and resistant to a chitinase digestion indicating structural differences from rhizobial Nod factors or mycorrhizal Myc-LCOs. We also investigated the presence of CgNINA and CgRHDF in 16 Frankia strains representative of Frankia diversity. High levels of root hair deformation (RHD) and activation of ProCgNIN were detected for Casuarina-infective strains from clade Ic and closely-related strains from clade Ia unable to nodulate C. glauca. Lower levels were present for distantly related strains belonging to clade III. No CgRHDF or CgNINA could be detected for Frankia coriariae (Clade II) or for uninfective strains from clade IV.